Quantifying load‐induced solute transport and solute‐matrix interaction within the osteocyte lacunar‐canalicular system. (17th April 2013) - Wang, Bin; Zhou, Xiaozhou; Price, Christopher; Li, Wen; Pan, Jun; Wang, Liyun
Abstract Osteocytes, the most abundant cells in bone, are essential in maintaining tissue homeostasis and orchestrating bone's mechanical adaptation. Osteocytes depend upon load‐induced convection within the lacunar‐canalicular system (LCS) to maintain viability and to sense their mechanical environment. Using the fluorescence recovery after photobleaching (FRAP) imaging approach, we previously quantified the convection of a small tracer (sodium fluorescein, 376 Da) in the murine tibial LCS under intermittent cyclic loading. In the present study, we first expanded the investigation of solute transport using a larger tracer (parvalbumin, 12.3 kDa), which is comparable in size to some signaling proteins secreted by osteocytes. Murine tibiae were subjected to sequential FRAP tests under rest‐inserted cyclic loading while the loading magnitude (0, 2.8, or 4.8 N) and frequency (0.5, 1, or 2 Hz) were varied. The characteristic transport rate k and the transport enhancement relative to diffusion (k/k0) were measured under each loading condition, from which the peak solute velocity in the LCS was derived using our LCS transport model. Both the transport enhancement and solute velocity increased with loading magnitude and decreased with loading frequency. Furthermore, the solute‐matrix interaction, quantified in terms of the reflection coefficient through the osteocytic pericellular matrix (PCM), was measured and theoretically modeled. The reflection coefficient of parvalbumin (σ = 0.084) was derived from the differential fluid and solute velocities within loaded bone. Using a newly developed PCM sieving model, the PCM's fiber configurations accounting for the measured interactions were obtained for the first time. The present study provided not only new data on the micro‐fluidic environment experienced by osteocytes in situ but also a powerful quantitative tool for future study of the PCM, the critical interface that controls both outside‐in and inside‐out signaling in osteocytes during normal bone adaptation and in pathological conditions. © 2013 American Society for Bone and Mineral Research.